2022
DOI: 10.1161/hypertensionaha.121.18369
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Antihypertensive Drug Class on Outcomes in SPRINT

Abstract: Background: The primary objective of this analysis is to assess if greater exposure to any major antihypertensive drug class was associated with reduced primary composite outcome events in SPRINT (Systolic Blood Pressure Intervention Trial). Methods: This is a secondary analysis of the SPRINT trial evaluating whether longitudinal, time varying exposure to any major antihypertensive drug class had any impact on primary outcome events, after adjusting for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 87 publications
0
9
0
Order By: Relevance
“…There has been debate about whether the choice of antihypertensive medications matters, but rather only that the blood pressure goal is achieved. There is now new data from the SPRINT trial 26 demonstrating that drug class influences outcomes post stroke with protective effects seen with thiazide type diuretics and angiotensin receptor blockers but a potential for harm with Beta blockers in this setting.…”
Section: Discussionmentioning
confidence: 99%
“…There has been debate about whether the choice of antihypertensive medications matters, but rather only that the blood pressure goal is achieved. There is now new data from the SPRINT trial 26 demonstrating that drug class influences outcomes post stroke with protective effects seen with thiazide type diuretics and angiotensin receptor blockers but a potential for harm with Beta blockers in this setting.…”
Section: Discussionmentioning
confidence: 99%
“… [36] In a different sub-study of the SPRINT trial, exposures of at least 1 year to thiazide diuretics and RAAS inhibitors were found to reduce adverse events and cardiovascular mortality; on the other hand, the use of beta-blockers was found to increase cardiovascular mortality. [37] Thus, along with consideration of improved cognitive function, other protective as well as risk factors, especially cardiovascular risk factors, should also be kept in mind while prescribing antihypertensive drugs to geriatric patients. Classes including ACEIs, ARBs, and CCBs may be superior to other drug classes, with effects not just limited to lowering blood pressure.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a post hoc analysis of the SPRINT study found that patients who received an ARB instead of a calcium channel blocker or beta-blocker for more than one year had a reduction in cardiovascular risk. 37 The advantage of an ARB could be its ability to improve arterial stiffness.…”
Section: Discussionmentioning
confidence: 99%